Determination of Primary School Teachers' Mathematical Gender Stereotypes and Examination of Their Reflection on Students - Ozge NURLU USTUN; Naciye AKSOY (Anı Publishing, 2022)
This study aims to investigate primary school teachers' mathematical gender stereotypes and to discover whether these stereotypes, if any, are reflected on students. The study was designed as a multiphase mixed methods study. Accordingly, in the quantitative and qualitative stages of the study, different sample groups including both fourth-grade teachers and fourth-grade students in Ankara were studied. Teachers' Gender Stereotype Scale toward Mathematics, observation form, Students' Gender Stereotype Questionnaire and Mathematics Achievement Test were sequentially used to collect data. The data were analyzed by Mann Whithey U test and content analysis. Results demonstrate that in comparision to the teacher who has neutral gender related beliefs toward mathematics, the teacher with strong traditional mathematical gender stereotypes favouring their male students. However, results show that students do not internalise their teachers' mathematical gender stereotypes, and, Hense, there is reflection of teachers' gender stereotypes on students' mathematical achievements. By carrying out longitudinal studies, it should be followed at which educational level students begin to acquire such gendered perspectives, which academic fields and professions they choose, and thus the effects of teacher characteristics on students should be revealed more comprehensively.